The impact of Ramadan fasting on metabolic control and biochemical profile of type 2 diabetic patients in Kubang Kerian, Kelantan - Yaacob, Nor Azwany (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
Introduction: Malaysia is an Islamic country with majority of the population is Muslim. Every year in Ramadan, the ninth month of Muslim calendar, a Muslim is required to fast everyday from the beginning of dawn until sunset. The average duration of fasting in Malaysia is 13.5 hours and during this period, a person is required to abstain from any oral intake including medications. Islam recommends that fasting Muslims eat a meal before dawn, called "sahur". Individuals are exempt from Ramadan fasting if they are suffering from an illness that could be adversely affected by fasting. They are allowed to restr.ain from fasting for one day to a1130 days, depending on the condition of their illness. People diagnosed with diabetes fall into this category and may be exempted from the fasting requirement. Earlier commentaries on the effect of fasting diabetics were mostly letters to editors reporting care reports and experience (Barber et al, 1979; Davidson, 1979; Aslam and Wilson, 1989). Barber et al (1979) reported half of the interviewed ·patients practice Ramadan fasting. The other half claimed exemption on medical grounds but insulin therapy is not an obvious reason. The insulin-treated patients noticed less glycosuria. They also did not notice any significant increased in hospital admission among those patients who choose to fast. In 1990, a local study by Mafauzy et al, shows significant difference between the means of body weight, serum fructosamine, total calorie intake, total carbohydrate intake and percentage of simple carbohydrate intake before and during Ramadan fasting. The significant fall in the serum fructosamine level implied that the overall glycemic control was significantly better during the fasting month than before. None of the patient had symptoms to suggest worsening of glycemic control. This study concluded that for noninsulin dependent diabetic patients, Ramadan fasting is possible and related to an improvement in the diabetic control.Rasheed (1992), in his overview on the fast of Ramadan, quoted two studies showing very little problems encountered by diabetics in Ramadan. Omar and Motala, 1997; recommended all diabetics to be evaluated before the month of Ramadan to assess their physical well being, metabolic control, and ability to keep fast. They added that a Muslim diabetic should be educated about special problems that may occur during fasting, as well as any therapeutic adjustments that may become necessary. Laajam, 1990, reported a study on overweight non-insulin diabetic patients, found no significant change in body weight, blood glucoseStudy Impact At local level, there is no information on what proportion of our diabetic patients that continue to fast, and what is their level of knowledge that they have for them to practice Ramadan fasting safely. We also lack of information on how they carry on with Ramadan fasting in terms of adjustment on drug regimen and alteration in dietary intake. Currently, there is no specific health education program for fasting diabetic. There is limited information on the impact of Ramadan fasting on biochemical profiles of type 2 diabetic patients. As discussed above, studies had shown that there is an improvement in diabetic control and body weight during Ramadan if they follow the prescribed diet. Information on these issues, as well as the impact of the one-month fasting in diabetics is essential to guide patients and medical professional regarding their safety and benefits of this practice. This study hopes to provide important informations for health care providers in educating and planning the management of diabetic patient during fasting month of Ramadan.